Challenges for Future Labour Markets Using the German Example Herausforderungen für die Arbeitsmärkte der Zukunft am Beispiel Deutschland - Fitzenberger, Bernd; Holleitner, Julia; Kagerl, Christian (Wirtschaftsdienst, 2024)
This article identifies the key challenges that the German labour market will face in the future.We discuss a number of approaches for successfully meeting these challenges, i.e.increasing mobility, agility, digitisation at the work place and the further flexibilisation of working conditions to allow people with care duties and older workers to remain available to the labour market for longer.
CRIS-Team Scopus Importer:2024-08-30